The gods below : the hollow covenant book 1 - Stewart, Andrea (Andrea G.) (Stewart, Andrea (Andrea G.). Hollow covenant, 2024)
"A divine war shattered the world leaving humanity in ruins. Desperate for hope, they struck a deal with the devious god Kluehnn: He would restore the world to its former glory, but at a price so steep it would keep the mortals indebted to him for eternity. And, as each land was transformed, so too were its people changed into strange new forms -- if they survived at all. Hakara is not willing to pay such a price. Desperate to protect herself, and her sister Rasha, she flees her homeland for the safety of a neighboring kingdom. But when tragedy separates them, Hakara is forced to abandon her beloved sister to an unknown fate. Alone and desperate for answers on the wrong side of the world, Hakara discovers she can channel the magic from the mysterious gems they are forced to mine for Kluehnn. With that discovery comes another: her sister is alive, and only the rebels plotting to destroy the God Pact can help rescue her. But only if Hakara goes to war against a god."--